Ever closer partnership : policy-making in US-EU relations - Philippart, Eric; Winand, Pascaline (Bruxelles : Presses Interuniversitaires Européennes Peter Lang, 2001)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: economische politiek; Europese Unie (EU).; Verenigde Staten van Amerika